Risk aversion and bank loan pricing - Gonzalo Camba-Méndez; Francesco Paolo Mongelli (European Central Bank (ECB), 2021)
How much of the heterogeneity in bank loan pricing is explained by disparities in banks' attitude towards risk? The answer to this question is not simple because there are only very weak proxies for gauging the degree of a bank's risk aversion. We handle this constraint by means of a novel econometric approach that allows us to disentangle the amount of risk faced by banks and the price they charge for holding that risk. Some of our results are aligned with previous studies and confirm that disparities in market power, banks' funding costs, and banks' funding risks are re ected in bank lending rates. However, our new modelling framework reveals that the heterogeneity in bank lending rates is also a re ection of the non-negligible disparities in banks' risk aversion.
Keywords: C23; E58; G21; 330; Bank loan pricing; risk aversion